Perception of Students about Tutorials in Open and Distance Learning at Allama Iqbal Open University (PJDOL, 2023)
This research study was conducted to find out the perceptions of students about tutorials in the Open and Distance Learning (ODL) at Allama Iqbal Open University (AIOU). The objectives of the study were to find out the perceptions of the students about tutorials in ODL at AIOU and to give suggestions for improvement in the tutorial system. In view of the time constraints, the study was consisted of the students involved at the Peshawar and Rawalpindi Regions of the AIOU in B.Ed. Course 512 of semester spring 2012.